Influence of muscle training in older inspiratory hypertensive inspiratory muscle weakness - Souza, Lillian Meirelly Cunha de (2014)
Introduction: It is common to the aging process the loss of respiratory muscle strength in heart and this process is most evident. Objectives: To measure the effects of a protocol of inspiratory muscle training in elderly hypertensive patients with respiratory muscle weakness. Materials and methods: This is a series of cases in which a protocol was applied using the Threshold ® IMT for five consecutive weeks. The evaluation included examinations of manometer, spirometry and 6MWT as well as the questionnaires Minichal and IPAQ (short version). For statistic we used t student test Results: The effectiveness of training in increasing the muscle strength was observed indirectly by the difference between the values of PImáxA (before) and PImáxD (after) training p = 0.004) . Conclusion: The training contributed to an increase in inspiratory muscle strength demonstrated by the increase in MIP, but its relationship with other variables measured is not clear.